Electrochemical synthesis of NiCo layered double hydroxide nanosheets decorated on moderately oxidized graphene films for energy storage - Jia, Dedong (2021)
The introduction of oxygenous functional groups onto graphene can provide additional pseudocapacitance for supercapacitors. However, how to balance the amount of introduced oxygenous functional groups and the reduced electrical conductivity arising from the disruption of the conjugated system remains a big challenge. Here, a controllable strategy is reported to prepare moderately oxidized reduced graphene oxide (MORGO) via an electrochemical oxidation process. The MORGO not only has oxygenous groups with appropriate quantities, but also preserves the highly crystalline structure of the π-π conjugated carbon framework. As a result, the MORGO films showed superior electrochemical properties to the pristine RGO films and other previously reported RGO films. Furthermore, the oxygenous groups and the conductivity of MORGO films can be easily adjusted by controlling the oxidation time. A hierarchical composite of NiCo-layered double hydroxide nanosheet arrays on MORGO films (MORGO/NiCo-LDH) was also constructed via electrochemical deposition to combine the advantages of electric double-layer electrode materials and faradaic electrode materials. The flexible solid-state supercapacitor fabricated with MORGO/NiCo-LDH film electrodes exhibits a high energy density (0.51 mW h cm⁻³), as well as a long cycle life (88.2% capacitance retention after 10 000 cycles).